Peningkatan Mutu Pembelajaran Melalui Optimalisasi Peran Guru Sebagai Manajer Kelas di SMP Negeri 1 Purwokerto - Siti Maesaroh (STAI Sufyan Tsauri Majenang, 2021)
The purpose of this study was to see the manager's ability, teachers' understanding of classroom management and the role of teachers as class managers to optimize the quality of learning at SMP Negeri 1 Purwokerto. This study used a qualitative approach with descriptive analysis, data techniques were carried out by interview, observation and documentation. The data analysis used consisted of data reduction, data collection and data retrieval. Sources of research data were school principals, teachers. The result of this research is that the role of teachers as class managers in SMP Negeri 1 Purwokerto can improve the quality of learning.